2013
DOI: 10.1021/es4016124
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Retention of Colloids in Porous Media: Does Shape Really Matter?

Abstract: The effect of particle shape on its transport and retention in porous media was evaluated by stretching carboxylate-modified fluorescent polystyrene spheres into rod shapes with aspect ratios of 2:1 and 4:1. Quartz crystal microbalance with dissipation (QCM-D) experiments were conducted to measure the deposition rates of spherical and rod-shaped nanoparticles to the collector (poly-l-lysine coated silica sensor) surface under favorable conditions. The spherical particles displayed a significantly higher deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 46 publications
(88 reference statements)
3
53
0
Order By: Relevance
“…More deposition of spherical colloids compared to rod-shaped colloids under favorable attachment conditions was reported from a quartz microbalance study (Seymour et al, 2013). Less rod-shaped particles were deposited under favorable conditions because greater hydrodynamic forces and torques counterbalance greater attractive forces of rod vs. spherical shaped particles (Seymour et al, 2013). However, less deposition of spherical colloids compared to rodshaped colloids was found for colloid transport under unfavorable attachment conditions in a porous medium made of glass beads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More deposition of spherical colloids compared to rod-shaped colloids under favorable attachment conditions was reported from a quartz microbalance study (Seymour et al, 2013). Less rod-shaped particles were deposited under favorable conditions because greater hydrodynamic forces and torques counterbalance greater attractive forces of rod vs. spherical shaped particles (Seymour et al, 2013). However, less deposition of spherical colloids compared to rodshaped colloids was found for colloid transport under unfavorable attachment conditions in a porous medium made of glass beads.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have been reported where the effect of colloid shape on colloid transport in porous media was investigated explicitly (Weiss et al, 1995;Salerno et al, 2006;Xu et al, 2008;Liu et al, 2010;Seymour et al, 2013), all of which were conducted with saturated porous media. Salerno et al (2006) compared the transport of spherical (1 µm diameter) and rod-shaped particles (made by stretching the spherical particles) in a medium made of glass beads.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of colloid retention in porous media for spherical and rod-shaped particles, Seymour et al 20 identified differences between particle-surface interaction energies, when the rod-shaped particles were oriented side-on vs. end-on with respect to the collector surface. While our model neglects any long-range particle-membrane interactions, the biased distribution of orientation angles predicted from our model and the results reported by Seymour et al 20 indicates that particle alignment may be important in particle attachment in environmental separations.…”
Section: Rejection Coefficientsmentioning
confidence: 99%
“…15 We, and others, have been interested in the effect of bacterial shape and flexibility on rejections from membrane filters. [19][20][21] It has been demonstrated that particle size, shape, and surface properties can play a role in nanoparticle separations and in their detection and environmental fate. 14,16 The impact of particle shape on transport in porous media and in attachment to environmentally relevant surfaces has also been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation